Evaluation of Tissue Response to Gore-Tex (Expanded Polytetrafluoroethylene) Implantation - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2013)
Objective/Hypothesis: The aim of this study was to assess the tissue response to Gore-Tex (expanded polytetrafluoroethylene) in rats and compare the results of surgical placement modalities. Study Design: Prospective animal study. Materials and Methods: Experiments were performed in 18 young Sprague-Dawley rats that were divided into 3 groups. Gore-Tex patches were implanted subcutaneously over the periosteum in the first group and under the periosteum in the other groups. Gore-Tex was immersed in an antibiotic-containing solution in the third group. All animals were killed 4 weeks after the procedure. The tissue samples were stained with hematoxylin and eosin stain and evaluated using a light microscope. Results: The Gore-Tex patches were displaced and not observed at the originally implanted sites in the first group. The Gore-Tex patches were observed at the originally implanted sites in the other groups. In group 1, edema and inflammation were prominent. In the second group, ossification was detected in 5 rats and foreign-body reaction and edema were identified in 1 rat. In the third group, all of the rats were found to have developed ossification, but no inflammatory reactions were observed. Conclusions: The results suggest that implanting synthetic graft materials immersed in an antibiotic solution at the subperiosteal plane provides better stabilization and low complication rates.
Keywords: Rhinoplasty; Gore-Tex; subperiosteal; augmentation; POROUS POLYETHYLENE IMPLANTS; NASAL RECONSTRUCTION; DORSAL AUGMENTATION; 6-YEAR EXPERIENCE; RHINOPLASTY; BIOMATERIALS